Efeito e custos do tratamento estratégico seletivo no controle de parasitoses gastrointestinais em bezerras leiteiras - Blanco, Yuly Andrea Caicedo (2015)
This study aimed at evaluating the effectiveness and costs of a selective strategic treatment for controlling gastrointestinal parasitoses in Holstein heifers. The experiment was conducted during the period from April of 2013 to November of 2014, at the Palmital Farm, of the Universidade Federal de Lavras, located in the municipality of Ijací, MG, Brazil. We equally divided 30 heifers into two groups: G1 – selective strategic treatment (ST), and G2 – conventional treatment (CT). In the CT, the control of parasitoses was performed according to orientation of the Veterinarian responsible for the Farm. In the ST of gastrointestinal helminths, we used Ranger® at 3.5% (ivermectin) during weaning (90 days of age), in the months of April, July, October and January, regardless of age, and individually, whenever the eggs per gram of feces (EPG) count was ≥300. For eimeriosis, we treated with Baycox® (toltrazuril at 5%) with 21 days of age, during weaning and individually, whenever the oocysts per gram of feces (OoPG) count was ≥500. For giardiasis, we used Panacur® (fenbendazole at 10%) at 21 days of age, during weaning and after 28 days. The heifers were monitored every 14 days, from birth to 12 months of age, by means of coproparasitological exams. The statistical analyses were performed using the SAS and PASW 2.0 statistical package. Regarding the level of helminthic infection (EPG), the ST (20.27%) presented global average of positive fecal samples (EPG ≥300) significantly lower (p<0.05) when compared to the CT (27.0%). In coproculture, the three most common nematode genera were Cooperia spp., Haemonchus spp, and Trichostrongylus spp. For coccidia infection (OoPG), the ST (17.26%) presented global average of positive fecal samples (OoPG ≥500) lower than in the CT (23.89%), however, with no significant difference (p<0.321; IC, 95%=1.036; 2.228). The heifers were infected by eight Eimeria spp. species, with E. bovis being the most frequent in both treatments. There was no significant difference (p>0.05) for Cryptosporium spp infection. The level of Giardia spp. significantly decreased in the ST (250 negative fecal samples), when compared to the CT (197). The fecal score (EC), the CT (19.16%) presented twice as many heifers with diarrhea when compared to the ST (9.68%). There was no significant difference (p>0.05) in average daily weight (ADW) gain between ST (580 g) and CT (570 g). The effective operational cost (EOC), per animal, during the entire experimental period, was approximately eight times higher in the ST (R$ 804.05) when compared to the CT (R$ 94.62). The factors which most influenced EOC were labor and laboratory exams. The ST reduced the level of infection by gastrointestinal nematodes, Eimeria ssp., Cryptosporidium spp. and G. duodenalis, in dairy heifers in the phases of breeding and raising, when compared to the CT.